Differences in Evolution of HIV-1 Subtype C Reverse Transcriptase Between Children and Adults Likely Explained by Maturity of Cytotoxic T-Lymphocyte Responses - Saravanan, Shanmugam (AIDS Res Hum Retroviruses, 2015)
In this study HIV-1 subtype C-infected adults demonstrated higher purifying selection on their viral populations in reverse transcriptase (RT) than infected children. This difference is likely explained by more mature cytotoxic T-lymphocyte responses in adults, which may have implications for the development of drug resistance in the RT region.